Evaluating the Expression of Wnt Pathway Related Genes in Mouse Vitrified Preantral Follicles: An Experimental Study - Sh Babaki; S Zavareh; P Farrok; M Nasiri (JRI, 2021)
Background: Wnt signaling pathway plays critical role in ovarian follicle development. Therefore, the aim of this study was to evaluate the effects of vitrification on the expression of Wnt pathway related genes in preantral follicles (PFs). Methods: Isolated PFs (n=982) of 14-16 day old female mice (n=45: 15 for each group) were divided into fresh (n=265), toxicity (n=272), and vitrified (n=265). The mRNA levels of Wnt2, Wnt4, Lrp5 and Fzd3 were evaluated by real-time PCR on the 2nd and 6th days of culture period. One-way ANOVA was conducted to analyze the data. Post hoc Tukey's HSD was used for multiple comparisons and p-value less than 0.05 was considered statistically significant. Results: The developmental parameters of fresh PFs were significantly higher than those of vitrified (p<0.001). There were no differences between fresh and vitrified PFs on the 2nd day of culture (p<0.001). Wnt4 expression levels decreased significantly in vitrified groups compared with fresh ones (p<0.001). Fzd3 and Lrp expression levels increased significantly in vitrified groups compared with those in the fresh group on the 2nd day (p<0.001). On the 6th day of culture period, the expression levels of Wnt2 and Fzd3 increased significantly in vitrified group compared to those of fresh group (p<0.001). Moreover, the expression levels of Wnt4 and Lrp increased significantly in toxicity groups compared to those of the control group (p<0.001). Conclusion: Vitrification increase the expression levels of Wnt2, Lrp and Fzd3 genes of PFs during in vitro culture.